Peace Efforts in the Divorce Cases: An Analysis on Verstek's Decision at the Religious Courts - Sudirman L Sudirman L; Andi Bahri S; Ahmad Faisal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
Indonesian national legal regulations requires judges to seek reconciliation between the parties effectively and optimally in each trial to prevent a divorce. However, in reality practice, these efforts have not been carried out optimally, so that some divorce cases increased from time to time in particular of verstek decisions, especially verstek decisions. This study aims to determine the implementation of peace efforts in divorce cases at the Parepare Religious Court, and to uncover the causes of non-achievement peace efforts so that a panel of judges decides in a verstek manner. This research applied empirical juridical method. The results of the study shows that the implementation of peace efforts at the Parepare Religious Court has not been effective and optimal in preventing divorce cases, especially in verstek case due to the judge's performance has not been maximized in seeking peace for every trial. In addition, the absence of one party with the intention to facilitate the divorce process as well as the desire of the parties to divorce has conducted a peace more difficult to achieve, in the end the judge set a verstek divorce decision.